2010
DOI: 10.1038/ncomms1151
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic observation of 'induced fit' in a cryptophane host–guest model system

Abstract: Cryptophane-A, comprised of two cyclotriguaiacylenes joined by three ethylene linkers, is a prototypal organic host molecule that binds reversibly to neutral small molecules via London forces. Of note are trifunctionalized, water-soluble cryptophane-A derivatives, which exhibit exceptional affinity for xenon in aqueous solution. In this paper, we report high-resolution X-ray structures of cryptophane-A and trifunctionalized derivatives in crown–crown and crown–saddle conformations, as well as in complexes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
90
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 45 publications
11
90
2
Order By: Relevance
“…This increase is explained by entropic (hydrophobic) effects that likely involve desolvation of xenon clathrates upon complexation. An increase of the binding constant can also be observed when the cavity is adjusted to the guest 16 . The D 3 -symmetric cryptophane-E (D 3 -1, see Fig.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…This increase is explained by entropic (hydrophobic) effects that likely involve desolvation of xenon clathrates upon complexation. An increase of the binding constant can also be observed when the cavity is adjusted to the guest 16 . The D 3 -symmetric cryptophane-E (D 3 -1, see Fig.…”
mentioning
confidence: 78%
“…The latter conformation has already been described for cryptophane-A derivatives and larger cryptophanes 16,28,29 . To determine the conformation of impl-1, a mixture of CHCl 3 @1 in 1,2-C 6 D 4 Cl 2 was heated at 423 K for 12 h to completely remove CHCl 3 from the solution.…”
Section: Determinationmentioning
confidence: 89%
See 1 more Smart Citation
“…90 Å 3 , assuming modest expansion from the average 4-Xe structure) (12) is approximately twice the radon atomic volume (35). Furthermore, in lieu of three ethylamine groups, tripropargylated 4 can be reacted with a wide variety of water-solubilizing azido linkers that may fine tune the host-noble gas interaction (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptophane-A, consisting of two cyclotriguaiacylene caps joined by three ethylene linkers, has been shown to encapsulate xenon reversibly as a host-guest complex (11). Recent X-ray crystallographic studies have shown that the internal volume of trisubstituted cryptophane-A derivatives can vary by more than 20%, depending on the size of the encapsulated guest (12). Several cryptophane-A derivatives have been synthesized and shown by isothermal titration calorimetry (ITC), fluorescence quenching, and NMR studies to exhibit xenon association constants as high as 33;000 AE 3;000 M −1 at 293 K in phosphate-buffered water (13)(14)(15)(16).…”
mentioning
confidence: 99%